Bone mineral density in moderate to severe asthmatic children treated with inhaled corticosteroids [İnhale kortikosteroidlerle tedavi edilen orta ve agir astimli çocuklarda kemik mineral yogunlugunun degerlendirilmesi] - (:unkn) unknown (My University, 2001)
Inhaled corticosteroids (ICS) are commonly used for patients with moderate to severe asthma. However, potential adverse effects on bone turnover is one of the greatest concerns of long-term ICS treatment. In the present study bone mineral density (BMD) was measured in 30 children (6-14 years) treated with ICS at a mean daily dose of 455 μg/day (200-1000) for 24-72 months and in 30 age-sex matched healthy controls using dual photon absorptiometry (DPA). There was no significant difference between asthmatics and controls for total BMD, spine, pelvis, arm and rib BMD. However leg and trunk BMD measurements were significantly lower in the asthmatic group (p=0.003 and p=0.02 respectively). Height in asthmatic children was significantly lower than in the control group (p=0.001). Although there was no significant difference in the daily calcium intake in both groups, this value was only 66 percent of the recommended daily allowance of calcium (RDA) in asthmatic group and 59 percent of the RDA in the control group. In conclusion in our study, decreased height and some regional BMD measurements in the asthmatic children may be partly related to low calcium intake. Peak bone density attained during prepubertal and pubertal years may be a critical determinant of fracture risk in adulthood. Maintainance of adequate calcium and vitamin D intake, close monitoring of growth, and bone mineral density measurement in asthmatic children receiving ICS agents may be helpful in determining and treating the possible adverse effect of the treatment on bone metabolism.
Keywords: Asthma; Bone mineral density; Inhaled corticosteroids